HUKUM GUGUR KARENA TIGA HAL - Sarino, Sarino; Aswanti, Wiwik (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This research discusses the relationship between law, power, and social resistance. The background of the research shows that a number of policies and legislative products? are considered not pro-people?and tend to benefit the rulers and businessmen, while the space for public participation in the law-making process is largely closed. The purpose of this study is to analyze the causes of the decline in the effectiveness of the law and the role of demonstrations and a means of socio-political correction, The method used is juridical normative with a study of related theories, concept, doctines, and legislation. The results of the study show that laws can be “overturned” or lose their legitimacy due to three main factor : (1) the law itself – reflected in problematic substance and prosedures as well as the judicial review decisions of the Constitutional Court; (2) power – political influence on the formation and amendment of laws, resulting in the laws often functioning as political tools; and (3) riots of demonstrations – historical mass actions have proven effective in driving social and legal change (e.g., the proclamation of independence, the 1998 reform, the labor movement). The conclusion emphasizes that changing the law requires a combination of political effort, legal mechanisms, and mass mobilization. The recommendations stress the importance of public participation in the legislative process, the use of available legal channel, and the strengthening of social movements as the corrective to policies that harm the people.